Giardia duodenalis Induces Proinflammatory Cytokine Production in Mouse Macrophages via TLR9-Mediated p38 and ERK Signaling Pathways - Pu, Xudong; Li, Xin; Cao, Lili; Yue, Kaiming; Zhao, Panpan; Wang, Xiaocen; Li, Jianhua; Zhang, Xichen; Zhang, Nan; Zhao, Zhiteng; Liang, Min; Gong, Pengtao (Frontiers in Cell and Developmental Biology, 2021)
Giardia duodenalis is an important opportunistic, pathogenic, zoonotic protozoan parasite, which is responsible for infections in the small intestines of humans and animals, causing giardiasis. Numerous previous studies have demonstrated that toll-like receptors (TLRs) in innate immunity are critical for the elimination of G. duodenalis, whereas for TLR9, the mechanism of innate immune responses mediated by it in host defense against Giardia infection remains unknown. In the present study, various methods of qRT-PCR, western blot, ELISA, IFA, inhibitor assays, and siRNA interference, were utilized to probe the role of TLR9 in mouse macrophages against GLV-free Giardia trophozoites or GLV-containing Giardia trophozoites. Our study revealed that with G. duodenalis stimulation, the secretion of pro-inflammatory cytokines including IL-6, TNF-α, and IL-12 p40 in mouse macrophages were enhanced, during which TLR9 was significantly activated, and block of TLR9 resulted in attenuated host inflammatory response. Remarkably, the presence of Giardia virus exacerbated secretion of host pro-inflammatory cytokines. Moreover, G. duodenalis stimulation could activate multiple signal pathways, including p38, ERK, AKT, and NF-κB p65, in which p38, ERK, and AKT pathways were activated dependent on TLR9. Additionally, inhibition of p38 or ERK pathway downregulated G. duodenalis-induced inflammatory response, while inhibition of AKT aggravated this process. Taken together, these findings implied that G. duodenalis may induce pro-inflammatory cytokines secretion by activating p38 and ERK signal pathways in a TLR9-dependent manner in mouse macrophages. The study on the mechanism of TLR9-mediated host inflammatory response in vitro may establish the foundation for an in-depth research on the role of TLR9 in pathogenicity of G. duodenalis.